2021
DOI: 10.1002/dc.24723
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Paris system for reporting urinary cytology with histologic follow‐up

Abstract: Background The Paris system (TPS) for Reporting Urinary Cytology provides a standardized reporting system whose main focus is the diagnosis of high‐grade urothelial carcinoma (HGUC). We conducted a study to see the impact of The Paris System on our cytologic diagnoses with associated histology. Materials and methods We reviewed our pathology database regarding urinary specimens in the year before implementation of The Paris System and the year after. We gathered the data regarding cytologic diagnosis and concu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…A study confirmed our result: after the LGUC diagnosis, subsequent cytology resulted in atypical, suspicious, or positive category in 51.9% of cases [32]. Very recently, another study subgrouped LGUC within the NHGUC category [33]. Within this category, concurrent histology was available in 50% of cases.…”
Section: Discussionsupporting
confidence: 78%
“…A study confirmed our result: after the LGUC diagnosis, subsequent cytology resulted in atypical, suspicious, or positive category in 51.9% of cases [32]. Very recently, another study subgrouped LGUC within the NHGUC category [33]. Within this category, concurrent histology was available in 50% of cases.…”
Section: Discussionsupporting
confidence: 78%
“…From its implementation, it has been shown to enhance correlation with histology, especially when the low urinary tract is sampled, while decreasing the indeterminate diagnoses [46,47]. Indeed, a few studies have demonstrated that TPS has reduced the rate of atypical interpretations reported in their departments [48][49][50][51]. This finding has a great clinical significance, as before the implementation of TPS, many urologists were regarding atypical cases as negative [6].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, TPS focuses on what is more important, which is the detection of HGUC [1,7]. Thus, it has established strict criteria for each one of its categories, including AUC, aiming to identify HGUC rather than LGUN, resulting in a frequency reduction in the "atypical" interpretations compared to the pre-TPS era [48][49][50][51]. Of interest, the pooled ROHM of the AUC reporting category in our meta-analysis was found to be 38.65% (95% CI, 0.3042; 0.4759), which should warrant close clinical follow-up and/or the use of ancillary testing [1,7], rather than being regarded as negative.…”
Section: Discussionmentioning
confidence: 99%
“…In the first group, Zare et al [38] reported that 2/52 (4%) LGUN cases were correctly classified post-TPS (vs. 6% pre-TPS); Meilleroux et al found that significantly fewer cases of LGUN were diagnosed post-vs. pre-TPS (0.9% vs. 1.8%), with sensitivities pre-and post-TPS of 31% and 10%, respectively, and specificities pre-and post-TPS of 96% and 100%, respectively [39]. Recently, Rohra et al reported similar rates of LGUN pre-vs. post-TPS (0.2% vs. 0.17%), but also placed 4% of their cases into a separate category of "Negative for high-grade, cannot rule out low-grade urothelial neoplasm", of which on follow-up, 67% were LGUN, 13% HGUC, and 20% negative [40]. The criteria for this category included 3D cellular clusters without fibrovascular cores.…”
Section: Tissue Fragments Arising From Low-grade Urothelial Neoplasms...mentioning
confidence: 99%